(X - 4 ) x 2 = X
You subtract X from four then you get your answer next to multiply your answer by two resulting in an answer….. the answer is the expression I wrote above.
√52-√13+√117
sqrt (4*13) - sqrt (13) + sqrt (13*9)
sqrt(4)sqrt(13) -sqrt(13)+sqrt(13)sqrt(9)
2sqrt(13) -sqrt(13)+3sqt(13)
sqrt(13)[2-1+3]
4sqrt(13)
Choice A
Answer:
17
Step-by-step explanation:
3x - 1; x = 6
3x - 1
3(6) - 1
18 - 1 = 17
<u>-TheUnknown</u><u>S</u><u>cientist</u>
M = 90 kg,
On Mars: g = 3.71 m/s²
Weight = m · g = 90 kg · 3.71 m/s² = 333.9 N
1 N = 0.2248 lbf
333.9 · 0.2248 = 75.06072 lbf ≈ 75 lbf
Answer is 82
substitute z for 9
9^2 = 81+ 1= 82